A articulação dos stakeholders diante do rompimento da barragem de Fundão em Mariana/M.G.: um estudo de caso - Oliveira, Elisângela Fátima de (2019)
It is known that the environment of a sudden disaster covers a range of factors that go beyond the techniques of analysis and response to disasters addressed in the most diverse studies of the area. In this regard, the dependence of action between different stakeholders (Stakeholders), creates among these a relationship of interdependence that is reflected in the execution of humanitarian operations in all stages of the humanitarian chain and which has special relevance during the reconstruction. Thus, the partnerships between governmental organizations, private agencies, humanitarian agencies and civil society in general can improve the quality and response of care provided to victims from the initial stages following the disaster to full recovery and reconstruction. Faced with this need, different strategies and instruments are developed in order to allow alignment of interests and expectations among stakeholders during the post-disaster reconstruction process. It should be emphasized that this process among the actors is characteristically dynamic and occurs in the different phases after disaster. In a comprehensive way, the study proposed to identify and map key stakeholders involved in the disaster that occurred with the Dam of Fundão during the recovery phase; analysing the tools and mechanisms present in the recovery phase as a means of identifying the relationships between the actors involved, as well as their interdependence and integration; characterize the governance structure proposed by the agreements as a way of coordinating the network of actors, models, instruments, and mechanisms present in the recovery phase as a means of identifying the relationships between the actors involved, as well as their interdependence and integration; characterize the governance structure proposed by the agreements as a way to coordinate the network of actors, models, instruments and arrangements derived from these relationships. The study considered such dynamism to analyze the specific case of the disaster in Mariana/MG. Focusing on the relationships between the actors involved in this municipality and their articulations, including the recovery phase in the time horizon that comprises three years after the occurrence of the disaster.